2018
DOI: 10.1007/s00011-018-1139-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of lymphotoxin-α in rheumatoid arthritis

Abstract: In this review, we summarize the key characteristics of LTα and the most recent findings on the role of LTα in RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…However, the involvement of LTα in inflammatory diseases is less well characterized than sTNF and a RA clinical trial using the anti-lymphotoxin-alpha antibody pateclizumab did not show statistically significant improvement in RA signs and symptoms (Kennedy et al, 2014). Differences between sTNF and LTα have been described elsewhere (Ruddle, 2014;Hirose et al, 2018). In this review, we will summarize the current knowledge of signal pathways emanating from the two TNFRs, their patho-/physiologic role and discuss recent promising results obtained in different disease models in the pre-clinical development of novel TNFR selective drugs.…”
Section: Introductionmentioning
confidence: 99%
“…However, the involvement of LTα in inflammatory diseases is less well characterized than sTNF and a RA clinical trial using the anti-lymphotoxin-alpha antibody pateclizumab did not show statistically significant improvement in RA signs and symptoms (Kennedy et al, 2014). Differences between sTNF and LTα have been described elsewhere (Ruddle, 2014;Hirose et al, 2018). In this review, we will summarize the current knowledge of signal pathways emanating from the two TNFRs, their patho-/physiologic role and discuss recent promising results obtained in different disease models in the pre-clinical development of novel TNFR selective drugs.…”
Section: Introductionmentioning
confidence: 99%
“…However, further studies revealed many differences between TNFβ and TNFα, especially in cell origin, secretion dynamics, signal transduction pathway, and gene expression regulation. Both TNFα and LTα can bind to TNF-receptors (TNFR1 or TNFR2); however, when LTα exists in heterotrimer form (LTα 1 β 2 or LTα 2 β 1 ), it can also bind to another unique receptor, the LTβ receptor (LTβR) [24]. In addition, the herpesvirus entry mediator (HVEM) may also act as a receptor for LTα [13].…”
Section: Discussionmentioning
confidence: 99%
“…LTA, also known as TNF-, mediates a large variety of inflammatory and immunostimulatory responses. 21 In vitro studies showed that LTA induced proliferation and inflammatory cascade signaling in RA synovial-fibroblasts (RASFs) and chondrocytes. 22,23 CD83, dendritic cell marker, belongs to the immunoglobulin superfamily and has previously been associated with autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%